In Vitro Characterization of Fluted Pumpkin Leaf Protein Hydrolysates and Ultrafiltration of Peptide Fractions: Antioxidant and Enzyme-Inhibitory Properties - Akinsola Albert Famuwagun; Adeola Monisola Alashi; Saka Olasunkanmi Gbadamosi; Kehinde Adekunbi Taiwo; Joseph Durodoluwa Oyedele; Odunayo Clement Adebooye; Rotimi Emmanuel Aluko (Polish Journal of Food and Nutrition Sciences)
Hydrolysates were produced using Alcalase (AH), chymotrypsin (CH), pepsin (PH), and trypsin (TH), and also fluted pumpkin leaf protein isolate (FLI) as a substrate. AH had the lowest degree of hydrolysis (16.37%) but exhibited overall superior antioxidant and enzyme inhibitory properties. Therefore, it was fractionated by membrane ultrafiltration to give 10 kDa peptide fractions. Gel permeation chromatography showed that the molecular weight of the FLI was 19.77 kDa and that of the hydrolysates was below 7.5 kDa. The hydrolysate peptides had a high content of hydrophobic amino acids but low levels of sulfur-containing amino acids, when compared to protein of FLI. Peptide sequence analysis showed that the hydrolysates consisted of dipeptides, tripeptides, and tetrapeptides with molecular weights below 500 Da. The hydrolysates were also stronger inhibitors of linoleic acid oxidation, α-amylase, α-glucosidase, and angiotensin converting enzyme (ACE) than FLI. Among the fractions, the <1 and 1-3 kDa were the most effective free radical scavengers and metal chelators in addition to their strong inhibitory activities against α-amylase, α-glucosidase, and ACE. We conclude that the AH and low molecular weight peptide fraction (<3 kDa) could find applications in formulating foods with various bioactive properties.